Will your next computer be a tin can and a wire? (Economist, 1995)
Some computer making firms and computer visionaries think that the Internet will be able to do much of the work done by today's computers and that it could end the reign of the personal computer (PC). If they are right, it would reshape the whole computer industry, making it a buccaneering competitive business once more. There are two main reasons that a growing camp within the industry thinks that the Internet can become a rival to the PC. The first reason is that tomorrow's networks will offer 10 million bits per second or more compared to 14,400 bits at present. The second reason is the emergence of Java, a new programming language, which was launched by Sun Microsystems in early 1995. Sun contends that programs written in this language could let users do everything that they do on their PC on the network. However, although specialized network computers may become popular, those who predict that such machines will kill the PC are ignoring computing history and “glitch-prone” real life.